Effect of Feed Flowrates on the Physical Properties and Antioxidant of Mahkota Dewa (Phaleria Macrocarpa) Encapsulated Powder - Muhammad Norzaman, Kathiman; Siti Kholijah, Abdul Mudalip; Jolius, Gimbun (IIUM Press, 2022)
This paper presents an experimental study on the encapsulation of Mahkota Dewa extracts by maltodextrin using spray drying. The bioactive compound from dried Mahkota Dewa was obtained using a subcritical water extraction process prior to a spray drying process. The effect of feed flow rate (485 to 2115 ml/h) was investigated using one-factor-at-a-time (OFAT). It was observed that the mean particle size increase varied from 3.55 to 8.38 µm when the feed flow rate increased from 485 to 2115 ml/h. Moisture content increased 4.88 to 6.83% as the feed flow rate increased from 485 to 2115 ml/h, whereas the antioxidant activity increased slightly from 90.48 to 91.65%. The findings from this study showed that decrease in feed flow rate reduces antioxidant activity, moisture content, and particle size.